Użyteczność jakościowych metod ewaluacji kapitału intelektualnego: The employment of qualitative methods of intellectual capital evaluation - Bombiak, Edyta (Management and Administration Journal, 2021)
The purpose of this article is to present a specific qualitative concept of intellectual capital measurement and its usefulness in its diagnosis and evaluation. Discussed are the nature, advantages and disadvantages of the most popular models of quality. Also presented is a proposal for an original component of intellectual capital measurement and a performance management process using a questionnaire.